Another Side of the Amudian Industry at Qesem Cave, Israel: The Southern Area Lithic Assemblage. (2nd October 2017) - Assaf, Ella; Barkai, Ran; Gopher, Avi
ABSTRACT: This paper describes the techno-typological affinities of a specific Acheulo-Yabrudian lithic assemblage dated to over 300 ka years ago from Qesem Cave, a middle Pleistocene site in central Israel. Aspects of blade production, knapping trajectories, and lithic recycling are examined in detail, demonstrating that this assemblage, notwithstanding its initial attribution to the blade-dominated Amudian industry, has some specific characteristics differing from other Amudian assemblages in the cave. The study discusses similarities and differences within the Amudian industry and offers a broader view of the variability within the Amudian industry of Qesem Cave.